Corporeidade e educação: sinfonia de saberes na educação musical - Silva, Valéria Carvalho da (2008)
This study investigates the implications between the musical theory and pedagogical practice based on a study that questions the reasons why some students feel incapable of learning the music language, as well as, if the musical codes are truly so difficult to be apprehended by them. To answer these questions takes itself as reference, the classes I have minister while teaching the disciplines: Music Workshop and Music Language I in the Art Department, Scenic Art Course at the Federal University of Rio Grande do Norte. I have searched the knowledge that constitutes the teacher formation based on the union between the pedagogical efficiency and sensibility, searching in the Corporality the theoretical port for my investigation. This way, advocating is a methodological principle for musical education originated from the experience of knowledge: creating, playing, feeling, thinking, and the interaction among them, conducting the students not only to music learning, but to a process of human formation. It adopts itself as methodological resource, amongst the qualitative methods, some of the techniques that are associated with the ethnographic research, for having as its main objective, to study the meaning of the actions and events of the investigated group. The analysis of the data leads to the conclusion that when the teacher displays his or her pedagogical knowledge in an environment constructed with affectivity, in a playful and pleasant form, the assimilation and construction of the musical concepts happen naturally and efficiently, surpassing the taboo that music learning is only possible to the especially well endowed people for music. Very aware that the scientific debate is important for the strengthening of formative programs involved in the growth and consolidation of the musical teaching and learning area, it is expected to promote this research discussions and reflections in the general educational field with this research, as well as, to contribute significantly to the specific growth of musical education